FOXL2 transcriptionally represses Sf1 expression by antagonizing WT1 during ovarian development in mice. Issue 5 (22nd January 2014) - Takasawa, Kei; Kashimada, Kenichi; Pelosi, Emanuele; Takagi, Masatoshi; Morio, Tomohiro; Asahara, Hiroshi; Schlessinger, David; Mizutani, Shuki; Koopman, Peter
ABSTRACT: Steroidogenic factor 1 (SF1; Ad4BP/NR5A1) plays key roles in gonadal development. Initially, the Sf1 gene is expressed in mouse fetal gonads of both sexes, but later is up‐regulated in testes and down‐regulated in ovaries. While Sf1 expression is activated and maintained by Wilms tumor 1 (WT1) and LIM homeobox 9 (LHX9), the mechanism of sex‐specific regulation remains unclear. We hypothesized that Sf1 is repressed by the transcription factor Forkhead box L2 (FOXL2) during ovarian development. In an in vitro system (TM3 cells), up‐regulation of Sf1 by the WT1 splice variant WT1‐KTS was antagonized by FOXL2, as determined by quantitative RT‐PCR. Using reporter assays, we localized the Sf1 proximal promoter region involved in this antagonism to a 674‐bp interval. A conserved FOXL2 binding site was identified in this interval by in vitro chromatin immunoprecipitation. Introducing mutations into this site abolished negative regulation by FOXL2 in reporter assays. Finally, in Foxl2 ‐null mice, Sf1 expression was increased 2‐fold relative to wild‐type XX fetal gonads. Our results support the hypothesis that FOXL2 negatively regulates Sf1 expression by antagonizing WT1‐KTS during early ovarian development in mice.—Takasawa, K., Kashimada, K., Pelosi, E., Takagi, M., Morio, T., Asahara, H., Schlessinger, D., Mizutani, S., Koopman, P. FOXL2 transcriptionally represses Sf1 expression by antagonizing WT1 during ovarian development in mice. FASEB J . 28, 2020–2028 (2014). www.fasebj.org